2016
DOI: 10.1002/chem.201602136
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Properties of Expanded Pyriporphyrins: A New Family of Alkylidenyl Porphyrin Homologues Bearing meso‐Exocyclic Double Bonds

Abstract: We present the synthesis and characterization of a new family of expanded meso-alkylidenyl (2,6-pyri)porphyrinoids bearing multiple exocyclic double bonds at the meso-positions. The synthesis was accomplished by using mixed pyrrole condensation. Similar to meso-alkylidenyl porphyrinoids, this study revealed that pyriporphyrinoids do not possess a porphyrin-like, global-aromatic character. The synthesized 2,6-pyripentaphyrin 1 displays selective ratiometric sensing of pyrophosphate anion in organic solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…2,6-pyridinedicarboxaldehyde; 2,3,5,6-tetramethyl-1,4- bis (trimethylsilyl)-1,4-diaza-2,5-cyclohexadiene ( F ), 2,5-dimethyl-1,4-bis­(trimethylsilyl)-1,4-diaza-2,5-cyclohexadiene ( G ) or 1,1′- bis (trimethylsilyl)-1,1′-dihydro-4,4′-bipyridine ( H ); and [( Mes Nacnac)­MgMg­( Mes Nacnac)] (where Mes Nacnac = [(2,4,6-Mes-C 6 H 3 -NCMe) 2 CH] − ) were prepared according to reported literature procedures. H 2 Mes,Ph L was prepared according to a modified literature procedure and has been recently reported by Milsmann et al in full detail .…”
Section: Methodsmentioning
confidence: 99%
“…2,6-pyridinedicarboxaldehyde; 2,3,5,6-tetramethyl-1,4- bis (trimethylsilyl)-1,4-diaza-2,5-cyclohexadiene ( F ), 2,5-dimethyl-1,4-bis­(trimethylsilyl)-1,4-diaza-2,5-cyclohexadiene ( G ) or 1,1′- bis (trimethylsilyl)-1,1′-dihydro-4,4′-bipyridine ( H ); and [( Mes Nacnac)­MgMg­( Mes Nacnac)] (where Mes Nacnac = [(2,4,6-Mes-C 6 H 3 -NCMe) 2 CH] − ) were prepared according to reported literature procedures. H 2 Mes,Ph L was prepared according to a modified literature procedure and has been recently reported by Milsmann et al in full detail .…”
Section: Methodsmentioning
confidence: 99%
“…exhibits novel physico‐chemical properties , , , . Another interesting modification of porphyrins/expanded porphyrins is to replace one or more five membered pyrrole rings with six membered heterocycles such as pyridine and the resulted pyridine containing porphyrinoids or pyriporphyrinoids would be expected to possesses unusual and different properties from regular pyrrole containing porphyrinoids , . A perusal of literature revealed that Berlin and Breitmaier in 1994 reported the first example of pyridine containing porphyrinoids and ever since several interesting pyridine incorporated porphyrinoids that includes regular,, , , , contracted, expanded, , , and heteroporphyrinoids were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Most expanded porphyrins rely on increasing the number of pyrrolic building blocks linked either directly via α–α linkages or through one C atom, such as the classic sapphyrin, , hexaphyrin H 2 1 , octaphyrin H 4 2 , or even larger architectures (Figure ). , Nonpyrrolic heterocycles (e.g., thiophene, furan, pyridine, or pyrazole) , or conjugated spacers such as phenylene or ferrocene may be incorporated into the macrocycle, illustrating the broad diversity of molecules classified as expanded porphyrins.…”
Section: Introductionmentioning
confidence: 99%